Two new species of Veigaia Oudemans (Acari : Veigaiidae) from India - Bhattacharyya, Asit K. (Zootaxa, 2006)
Two new species, Veigaia tricuspidata sp. nov. and V. sisiri sp. nov., are described and illustrated from India, on the basis of the adult females. A key to the six Indian species of Veigaia Oudemans is provided.